(untitled) (Annals of Medical Research, 2023)
Aim: Crush injury damages the nerve, affects its function and causes oxidative stress. Alpha-lipoic acid (ALA) is an antioxidant agent with protective effects on the nerve tissue. In this study, we aimed to investigate the effects of ALA in the treatment of crush sciatic nerve injury in rats. Materials and Methods: Forty rats were divided into five groups. Walking Track Analysis (WTA) was performed in all groups before sacrificing the sciatic nerve. In group I (sham group), the sciatic nerve was exposed but not crushed, whereas in group II (early control group, 24th hour), group III (late control group, 7th day), group IV (early experimental group, 24th hour), and group V (late control group, 7th day), the sciatic nerve was exposed and clipped with an aneurysm clip for 300 seconds. One hour after the crush injury, subjects in groups II and III were given saline (2.5 ml, intraperitoneally), while ALA (100 mg/kg, intraperitoneally) was administered in Groups IV and V. WTA was performed in Groups I, II, and IV at the 24th hour after clipping and was performed in Groups III and V at 7th day after clipping. In all groups, the Sciatic Functional Index (SFI) was calculated after WTA. Following the completion of WTA, sciatic nerve tissue samples were obtained for the measurement of malondialdehyde (MDA), superoxide dismutase (SOD), glutathione peroxidase (GSH-Px) and catalase (CAT) enzyme values. Results: The SFI scores in groups II, III, IV, and V were significantly lower than that of sham group (p˂0.05), while no significant difference was found between groups II and IV and between groups III and V (p>0.05). The CAT values of groups II and IV, the GSH-Px value and MDA value of group IV, and the SOD values of groups II and IV were found to be significantly higher than those of sham group (p<0.05). However, no significant difference was found among groups I, III, and V with regard to CAT, GSH-Px, MDA and SOD values (p>0.05). Conclusion: The results indicated that a single dose of ALA (100 mg/kg) administered intraperitoneally one hour after the sciatic nerve crush injury had no therapeutic efficacy at 24 hours and 7 days after the administration. Further experimental studies are needed to evaluate the effectiveness of ALA applied in several doses rather than a single dose in crush peripheral nerve injury models.